2017
DOI: 10.1007/s00484-017-1441-y
|View full text |Cite
|
Sign up to set email alerts
|

Spa therapy adjunct to pharmacotherapy is beneficial in rheumatoid arthritis: a crossover randomized controlled trial

Abstract: This study aims to investigate whether 2-week spa therapy, as an adjunct to usual pharmacological therapy, has any beneficial effect in patients with rheumatoid arthritis (RA). In this single-blind crossover study, 50 patients were randomly assigned in a 1:1 manner to receive usual pharmacological therapy plus 2-week spa therapy or usual pharmacological therapy alone (period 1.6 months); after a 9-month washout, patients were crossed over to the opposite assignment (period 2.6 months). Spa therapy program incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 55 publications
0
23
0
3
Order By: Relevance
“…Nowadays, several human in vivo studies demonstrated the efficacy of BT [ 1 – 3 , 9 , 48 , 49 ]. Randomized controlled clinical trials investigated OA of the knee [ 50 , 51 ], hip [ 52 ], or shoulder [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, several human in vivo studies demonstrated the efficacy of BT [ 1 – 3 , 9 , 48 , 49 ]. Randomized controlled clinical trials investigated OA of the knee [ 50 , 51 ], hip [ 52 ], or shoulder [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effective substances of the Hévíz mud were described previously [ 4 – 6 ]. BT is widely used to amplify the effects of drug treatments and recommended for a broad spectrum of diseases, such as arthritis, dermatitis, and fibromyalgia [ 7 9 ]. The efficacy of BT for osteoarthritis has been approved by several randomized clinical trials but beneficial actions of this treatment are often manifested in subjective improvements of the pain sensation and the quality of life [ 1 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…4b, Additional file 5: Figure S5B). This change in temperature-comfort relationship is reminiscent of the preference of human patients with RA for warm baths (36–37 °C), which relieve pain and provide a basis for conventional spa therapy [32, 33]. It is thus speculated that the increased preference for a warm temperature observed in the CIA mice in this study might reflect the subjective “feeling” of animals that a warmer temperature can reduce nociceptive sensation.…”
Section: Discussionmentioning
confidence: 80%
“…Most of the balneotherapeutic studies abroad have never used a placebo control (15,16,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), despite the fact that this would be one of the most important steps in proving the beneficial effects of medicinal waters. In Hungarian studies, it is more common to use a placebo control (4,7,(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%